Genetic analysis of paprika genotypes for dry fruit yield in chilli - Kumar, S Srikanth, V Kanthaswamy, S Ramesh (Journal of Spices and Aromatic Crops, 2016)
Ten genotypes of paprika were evaluated for mean performance, variability parameters and association of characters towards dry fruit yield. Based on mean performance, genotype C-6 (‘U.S.609’) was the best for all characters except number of seed fruit-1, ascorbic acid, oleoresin content, capsaicin and capsanthin content. High estimates of genotypic coefficients of variation for numbers of primary branches, dry fruit yield plant-1, fresh ripe fruit yield plant-1 and fruit length indicated that the major part of variability was due to genetic makeup for these traits. Fruit length, fresh ripe fruit yield plant-1 and dry fruit yield plant-1 had higher genetic advance coupled with high heritability indicates the additive gene action. Among the characters analyzed for association it could be concluded that number of fruit plant-1, fruit length, plant height, days from anthesis to harvest and number of primary branches plant-1 would be appropriate selection parameters for improvement of fresh fruit yield.